MODEL KURIKULUM TERINTEGRASI ILMU EKONOMI DAN ISLAM SERTA IMPLEMENTASINYA DALAM PROSES PEMBELAJARAN - Kadar M. Yusuf; Alwizar Alwizar; Irawati Irawati (Risâlah, Jurnal Pendidikan dan Studi Islam, 2020)
Three are three main problems to focus of this research. First, the form of learning tools for Economics is integrated with Islamic sharia, which includes Semester Learning Plans (RPS) and modules. Second, the use of these two tools in learning. Furthermore, the third evaluation of the results of its use, which is found in students, which includes asking them to learn it and their mastery of teaching material. This research uses the R & D research model, which begins with designing the RPS and Economics Economics modules integrated with Islamic shariah and then implemented in learning. The results of the study illustrate that the RPS (teaching plan) was successfully designed by incorporating it into the integration model of Economics with Shari'ah, which includes three alternatives namely Al-Nushush al-Syar'iyah (Syariah Texts), Al-Tahlil al-Syar`i (Islamic law Analysis), and Al-Naqd al-Syar`i (Islamic law Critics). Likewise, the learning module for Economics is integrated with Islamic sharia, it has also been successfully formulated. In addition to the RPS and modules, the results of the study also showed that the lecturer supporting the course was able to convey Islamic sharia in relation to the material being taught. Likewise, students, they are very enthusiastic about taking Economics lectures that are integrated with Islamic sharia. It can be seen in their very high interest in taking this course, as well as their excellent learning outcomes.